Still a Hard-to-Reach Population? Using Social Media to Recruit Latino Gay Couples for an HIV Intervention Adaptation Study - Martinez, Omar; Wu, Elwin; Shultz, Andrew Z; Capote, Jonathan; López Rios, Javier; Sandfort, Theo; Manusov, Justin; Ovejero, Hugo; Carballo-Dieguez, Alex; Chavez Baray, Silvia; Moya, Eva; López Matos, Jonathan; et al. (JMIR Publications, 2014)
BackgroundOnline social networking use has increased rapidly among African American and Latino men who have sex with men (MSM), making it important to understand how these technologies can be used to reach, retain, and maintain individuals in care and promote health wellness. In particular, the Internet is increasingly recognized as a platform for health communication and education. However, little is known about how primarily Spanish-speaking populations use and engage with each other through social media platforms. ObjectiveWe aimed to recruit eligible couples for a study to adapt "Connect 'n Unite" (an HIV prevention intervention initially created for black gay couples) for Spanish-speaking Latino gay couples living in New York City. MethodsIn order to successfully design and implement an effective social media recruitment campaign to reach Spanish-speaking Latino gay couples for our ongoing "Latinos en Pareja" study, our community stakeholders and research team used McGuire's communication/persuasion matrix. The matrix guided our research, specifically each marketing "channel", targeted "message", and target population or "receiver". We developed a social media recruitment protocol and trained our research staff and stakeholders to conduct social media recruitment. ResultsAs a result, in just 1 month, we recruited all of our subjects (N=14 couples, that is, N=28 participants) and reached more than 35,658 participants through different channels. One of the major successes of our social media recruitment campaign was to build a strong stakeholder base that became involved early on in all aspects of the research process-from pilot study writing and development to recruitment and retention. In addition, the variety of "messages" used across different social media platforms (including Facebook, the "Latinos en Pareja" study website, Craigslist, and various smartphone applications such as Grindr, SCRUFF, and Jack'd) helped recruit Latino gay couples. We also relied on a wide range of community-based organizations across New York City to promote the study and build in the social media components. ConclusionsOur findings highlight the importance of incorporating communication technologies into the recruitment and engagement of participants in HIV interventions. Particularly, the success of our social media recruitment strategy with Spanish-speaking Latino MSM shows that this population is not particularly "hard to reach", as it is often characterized within public health literature.